PENGARUH EDUKASI MANAJEMEN HIPERTENSI BERBASIS BOOKLET TERHADAP PENGETAHUAN LANSIA PENDERITA HIPERTENSI - R.A Fadila; Syafariza (Jurnal Kesehatan dan Pembangunan, 2025)
Hypertension is known as The Silent Killer because it often occurs without symptoms, leading many individuals to be unaware of their condition until complications arise. Education using booklet media can improve the elderly's adherence to self-care and encourage healthy lifestyle changes to prevent such complications.This study aimed to determine the effect of booklet-based hypertension management education on the knowledge of elderly patients. Using a one-group pre-test and post-test design, the study involved 30 respondents. Results showed an increase in average knowledge scores from 12.30 to 13.32, with a p-value of 0.001 (<0.05), indicating a significant effect of booklet education on improving elderly knowledge. These findings are expected to serve as a reference for health workers in providing more effective education on hypertension management to elderly patients.